NF-κB and AP-1 Activation by Nitric Oxide Attenuated Apoptotic Cell Death in RAW 264.7 Macrophages - von Knethen, Andreas (The American Society for Cell Biology, 1999)
A toxic dose of the nitric oxide (NO) donor S-nitrosoglutathione (GSNO; 1 mM) promoted apoptotic cell death of RAW 264.7 macrophages, which was attenuated by cellular preactivation with a nontoxic dose of GSNO (200 μM) or with lipopolysaccharide, interferon-γ, and N(G)-monomethyl-l-arginine (LPS/IFN-γ/NMMA) for 15 h. Protection from apoptosis was achieved by expression of cyclooxygenase-2 (Cox-2). Here we investigated the underlying mechanisms leading to Cox-2 expression. LPS/IFN-γ/NMMA prestimulation activated nuclear factor (NF)-κB and promoted Cox-2 expression. Cox-2 induction by low-dose GSNO demanded activation of both NF-κB and activator protein-1 (AP-1). NF-κB supershift analysis implied an active p50/p65 heterodimer, and a luciferase reporter construct, containing four copies of the NF-κB site derived from the murine Cox-2 promoter, confirmed NF-κB activation after NO addition. An NF-κB decoy approach abrogated not only Cox-2 expression after low-dose NO or after LPS/IFN-γ/NMMA but also inducible protection. The importance of AP-1 for Cox-2 expression and cell protection by low-level NO was substantiated by using the extracellular signal-regulated kinase inhibitor PD98059, blocking NO-elicited Cox-2 expression, but leaving the cytokine signal unaltered. Transient transfection of a dominant-negative c-Jun mutant further attenuated Cox-2 expression by low-level NO. Whereas cytokine-mediated Cox-2 induction relies on NF-κB activation, a low-level NO–elicited Cox-2 response required activation of both NF-κB and AP-1.